2009
DOI: 10.1038/ijo.2009.43
|View full text |Cite
|
Sign up to set email alerts
|

A structural equation model relating adiposity, psychosocial indicators of body image and depressive symptoms among adolescents

Abstract: Objective: Psychosocial factors, including pressure to be thin and body dissatisfaction, have been hypothesized to mediate the relationship between obesity and depression, especially during adolescence when vulnerability to social pressures around body shape and image is heightened. The objective was to test a model of the relationships among adiposity, psychosocial factors and depression in adolescents. Method: In a population-based sample of 1127 boys and 1167 girls aged 13 and 16 years, a model of the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 38 publications
3
35
1
Order By: Relevance
“…It was the attempt to diet or failure to lose weight by dieting, rather than weight status that caused depressive symptoms. Chaiton et al [6] concluded that adiposity was related to depressive symptoms through body dissatisfaction and pressure to be thin, which was consistent with our findings.…”
Section: Dietingsupporting
confidence: 93%
See 2 more Smart Citations
“…It was the attempt to diet or failure to lose weight by dieting, rather than weight status that caused depressive symptoms. Chaiton et al [6] concluded that adiposity was related to depressive symptoms through body dissatisfaction and pressure to be thin, which was consistent with our findings.…”
Section: Dietingsupporting
confidence: 93%
“…However, both obesity and depression are heterogeneous diseases, and not all obese individuals develop psychological consequences. Recent studies have shown that obese individuals with some risk factors, such as severe obesity [29], teasing [37], body image [1,6,19], and dieting history [9], are more likely to develop depression than normal weight individuals. Our study demonstrated that overweight perception, weight concern, and dietary restraint were also important mediating factors.…”
Section: Obesity and Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two other studies have also reported associations between depressive symptoms and adiposity only in girls (Chaiton et al, 2009;Hillman et al, 2010). A possible mechanism underlying the gender differences between anxious-depressive scores and adiposity at age 14 may be sex-related differences in hormones such as leptin.…”
Section: Discussionmentioning
confidence: 92%
“…Evidence from prospective studies suggests that the relations between depression and obesity are bidirectional (4,5). Depressive symptoms have traditionally been examined as a consequence of obesity reflecting the stigma and discrimination that obese people encounter (58) and body dissatisfaction could be one pathway in this relation (59,60). To our knowledge, this is the first study to show that emotional eating and PA self-efficacy may act as pathways when considering weight gain as a consequence of depressive symptoms, but further prospective studies are needed to confirm the causality of these relations and to examine whether there are other behavior-specific psychosocial mediators.…”
Section: Discussionmentioning
confidence: 99%